How molecular advances may improve the diagnosis and management of PTCL patients - Drieux, Fanny; Lemonnier, François; Gaulard, Philippe (Frontiers in Oncology, 2023)
Peripheral T-cell lymphomas (PTCL) represent 10 to 15% of adult non-Hodgkin lymphomas. In the latest revised WHO and ICC classifications (1,2), more than 30 entities are described, mostly defined by their clinical and pathological and phenotypic features, with a growing element of molecular data. Indeed, molecular studies based on high-throughput technologies have allowed for a better understanding of the oncogenic mechanisms involved and have improved the characterization of several entities. Although only a few specific genomic alterations define a given entity, the use of molecular data, such as clonality assays and targeted next-generation sequencing (NGS), is now integrated into the routine diagnostic workflow of expert centers, in combination with clinical and pathological clues. However, the translation of high-throughput genomic studies to clinical practice is still limited due to the high cost of high-throughput technologies and little clinical relevance for most findings. In this review, we will detail the oncogenic mechanisms of the main non-cutaneous PTCL entities, the molecular targets that have an impact on their diagnosis or treatment, and the assays that are useful for the detection of these clinically relevant molecular alterations(3). Entities with a leukemic presentation (notably T-cell large granular lymphocytic leukemia and T-prolymphocytic leukemia) will not be detailed.